Pengelolaan Sosial Media Marketing Terhadap Brand Awareness Dan Consumer Interest Di PT. Telkom Witel Bandung - Daliarni, Ni Putri; Halim, Prihartono Aksan (Universitas Hamzanwadi, 2023)
Current technological developments that affect the marketing world are the background of this research. So, we conducted research to identify how much influence social media marketing management has on brand awareness and consumer interest in PT Telkom Witel Bandung. Through the data that has been processed for this research. The methods chosen are the causal quantitative method and the probability sampling technique. The sample used was 100 respondents who came from all individuals who had seen promotions on PT Telkom Witel Bandung's social media. For data collection, the method used is a questionnaire on a Likert scale. The analysis techniques used are descriptive analysis, classical assumption test, partial test (t), simultaneous test (F), and coefficient of determination test (R2). The test results obtained a sig. value in the t-test and f-test of 0.000, which means that the value is < 0.05, proving that there is a significant influence of social media marketing management on brand awareness and consumer buying interest. Companies need to continue to be consistent in managing social media marketing because it can have an impact on sales for the company, and if developed consistently, it can generate high profits and can continue to increase